Development and investigation of the applicability of computed tomography data-based modelling technique for polymeric high-density foams. Issue 2 (March 2022) - Hössinger-Kalteis, Anna; Reiter, Martin; Jerabek, Michael; Major, Zoltan
As foams have become very important in several areas and since characterizing their properties is a crucial task, a finite element simulation model for high-density closed cell foams based on computed tomography (CT) measurements is developed. The model includes realistic microstructural features like cell size distribution due to the utilization of CT data. Moreover, a 'skin-core-skin' microstructure resulting from the manufacturing process (injection moulding) of the foams is also considered in the model. The mechanical behaviour of the foam's core layer under tension and compression load is characterized based on the microstructural model to develop constitutive material models of the foam. These constitutive models enable further mechanical characterization of the foam with less computational effort. Compression and bending test simulations of injection moulded foams with three different densities are validated with corresponding experimental results. Thus, conclusions can be drawn regarding the reliability, applicability and possible further extensions of the high-density foam model.